2018
DOI: 10.1097/jtn.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Population Health Data on Violence Into the Emergency Department: A Feasibility and Implementation Study

Abstract: Geocoded emergency department (ED) data have allowed for the development and evaluation of novel interventions for the prevention of violence in cities outside of the United States. First implemented in Cardiff, United Kingdom, collection of these data provides public health agencies, community organizations, and law enforcement with place-based information on assaults. The purpose of this study was to assess the feasibility of translating this model within the electronic medical record (EMR) in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Other ongoing challenges include continuing financial support for a VPC, maintaining high nursing participation in screening and expanding the CMST to more comprehensively include all critical care and trauma patients. Nurse participation in the satisfaction survey may be considered low (51%), although this is a similar past response rate when the survey was implemented in a different US hospital 22. The hospital’s primary role is to provide care, thus, medical care needs must first be met and then CMST data collection may occur among critical care and trauma patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Other ongoing challenges include continuing financial support for a VPC, maintaining high nursing participation in screening and expanding the CMST to more comprehensively include all critical care and trauma patients. Nurse participation in the satisfaction survey may be considered low (51%), although this is a similar past response rate when the survey was implemented in a different US hospital 22. The hospital’s primary role is to provide care, thus, medical care needs must first be met and then CMST data collection may occur among critical care and trauma patients.…”
Section: Discussionmentioning
confidence: 98%
“…Minor US adaptations include word choices (eg, bar vs pub) and item ordering. Other US-based Cardiff Model projects may want to consider collecting information on unintentional injuries to inform public health prevention strategies (see the Wisconsin adaptation) 22…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior pilot studies from around the globe demonstrated Cardiff Model feasibility and adequate patient information collection about assaultive injuries in the healthcare setting. [11][12][13][14] Information collected includes time and location of the assault, and weapon(s) used. This information is then deidentified, aggregated and analysed in tandem with law enforcement data.…”
Section: Current Approaches For Violence Preventionmentioning
confidence: 99%